Uric acid and adiponectin in cardiovascular disease - Norvik, Jon Viljar (UiT The Arctic University of Norway, 2017)
The papers 2 and 3 of this thesis are not available in Munin. Paper 2: Norvik, J. V., Schirmer, H., Ytrehus, K., Storhaug, H. M., Jenssen, T. G., Eriksen, B. O., Mathiesen, E. B., Løchen, M. L., Wilsgaard, T., Solbu, M. D.: “Uric Acid Predicts Mortality and Ischaemic Stroke in Subjects with Diastolic Dysfunction: The Tromsø Study 1994- 2013”. (Manuscript). Published version available in ESC Heart Fail. 2017 May; 4(2): 154–161. Paper 3: Norvik, J. V., Schirmer, H., Ytrehus, K., Jenssen, T. G., Zykova, S. N., Eggen, A. E., Eriksen, B. O., Solbu, M. D.: “Low Adiponectin is Associated with Diastolic Dysfunction in Women: a Cross-sectional Study from The Tromsø Study”. (Manuscript). Published version available in BMC Cardiovasc Disord. 2017; 17: 79. Uric acid, a product of metabolism, was discovered a quarter of a millennium ago and has been known to be a possible cardiovascular risk factor for well over a century. A much newer discovery, adiponectin, was discovered only a little more than 20 years ago as a protein hormone secreted by adipose tissue and has attracted substantial attention for its association with cardiovascular disease. This thesis will examine the modifying action of overweight on the relationship between uric acid levels and metabolic syndrome, the association between uric acid levels and adverse cardiovascular events and mortality in subjects with or without diastolic dysfunction, and the sex-specific association between adiponectin levels and diastolic dysfunction. In addition, this thesis will determine whether a relevant interaction between uric acid and adiponectin exists with respect to diastolic dysfunction. Paper 1, a seven-year prospective study with over 6,000 participants, examines whether overweight modifies the association between the uric acid levels and metabolic syndrome. In overweight but not normal-weight subjects, the baseline uric acid levels predicted the development of elevated blood pressure and elevated fasting glucose levels. The baseline uric acid levels and changes in ...